Magnetic levitation in orbitron system - Zub, S.S. (Вопросы атомной науки и техники, 2014)
This paper devoted to proof the existence of stable quasi-periodic motions of the magnetic dipole that is under the action of the external magnetic field and homogeneous field of gravity. For proof we used energy-momentum method that is the group-theoretic method of Hamiltonian mechanics. Numerical simulation shows the possibility of realization of stable motions with physically reasonable parameters of the system. Доказана возможность устойчивых квазипериодических движений магнитного диполя, находящегося под действием как внешнего магнитного поля, так и однородного поля силы тяжести. Для доказательства используются теоретико-групповые методы гамильтоновой механики, а именно: energy-momentum метод. Численное моделирование демонстрирует возможность реализации устойчивых движений при физически разумных параметрах системы. Доведено можливiсть стiйких квазiперiодичних рухiв магнiтного диполя, що знаходиться пiд дiєю як зовнiшнього магнiтного поля, так i однорiдного поля сили тяжiння. Для доведення використовуються теоретико-групповые методи гамiльтонової механiки, а саме: energy-momentum метод. Чисельне моделювання демонструє можливiсть реалiзацiї стiйких рухiв для фiзично прийнятних параметрах системи.